MANAJEMEN PEMBELAJARAN GURU BERBASIS TEKNOLOGI PADA KOMUNITAS BELAJAR DI SEKOLAH MENENGAH ATAS (SMA) KABUPATEN ACEH TENGGARA - Vesfi Yulia; Hera Yanti; Aminah Aminah (Hijri, 2026)
This study aims to describe the management of teacher learning based on Technological Pedagogical Content Knowledge (TPACK) within teacher learning communities at Senior High Schools (SMA) in Aceh Tenggara Regency. This research employed a qualitative approach with a descriptive research design. The research subjects included principals, teachers, and learning community facilitators at SMA Negeri 1 Kutacane and SMA Negeri 3 Kutacane. Data were collected through interviews, observations, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that: (1) in the planning stage, TPACK-based learning at SMA Negeri 1 Kutacane and SMA Negeri 3 Kutacane was designed through the development of teacher learning community programs, planning of TPACK training, guidance in selecting instructional media and technology, and the formulation of school policies supporting TPACK integration; (2) in the implementation stage, principals in both schools played an active role in facilitating TPACK training and workshops, encouraging teacher collaboration within learning communities, supervising the implementation of technology-based learning, and providing supporting technological facilities and infrastructure; and (3) in the evaluation stage, the implementation of TPACK at SMA Negeri 1 Kutacane and SMA Negeri 3 Kutacane was monitored through classroom supervision and observation, followed up by addressing challenges in technology use, utilized as a basis for improving instructional planning, and documented in evaluation reports to support the development of teacher learning communities. The findings indicate that the management of TPACK-based teacher learning within learning communities at senior high schools in Aceh Tenggara Regency has been implemented systematically and sustainably through principal leadership, teacher collaboration, and school management support. Therefore, the implementation of TPACK does not solely depend on individual teacher competence, but is strongly influenced by well-directed and sustainable management of teacher learning communities